A phase 4, open-label study to evaluate the safety and immunogenicity of DTaP5-HBV-IPV-Hib in children previously vaccinated with DTaP2-HBV-IPV-Hib or DTaP5-HBV-IPV-Hib (V419-016) - Andrea Guerra; Claudio Costantino; Federico Martinon-Torres; Soeren Westerholt; Courtney Lambeth; Ziqiang Chen; Jessie Lumley; Tomas Marcek; David Johnson; Marissa Wilck (Human Vaccines & Immunotherapeutics)
DTaP5-HBV-IPV-Hib (Vaxelis®) is a hexavalent combination vaccine (HV) indicated in infants and toddlers for the prevention of diphtheria, tetanus, pertussis, hepatitis B, poliomyelitis, and invasive disease due to Haemophilus influenzae type b. Switching between HVs during the childhood vaccination series is sometimes necessary due to, for example, vaccine availability, health-care provider preference, and/or tender awards. The purpose of this study was to describe the safety, tolerability, and immunogenicity of a booster dose of Vaxelis® in participants who previously received a primary infant series of either DTaP2-HBV-IPV-Hib (Hexyon®) or Vaxelis®. Healthy participants approximately 11–13 months of age who previously received a two-dose primary series of Hexyon® (HHV group) or Vaxelis® (VVV group) all received a Vaxelis® booster dose. Immunogenicity was evaluated by measuring antibody levels to individual vaccine antigens approximately 30 days following booster vaccination. Safety was evaluated as the proportion of participants with adverse events (AEs). The proportions of participants with antibody-specific responses for antigens contained in both Vaxelis® and Hexyon® at 30 days post-toddler-booster vaccination with Vaxelis® were comparable between groups, and higher in the VVV group for Vaxelis® antigens PRN and FIM2/3. The overall proportions of participants with AEs were generally comparable between groups. Following a booster dose of Vaxelis®, immune responses were comparable between groups for all shared antigens, and higher in the VVV group for antigens found only in Vaxelis®. The booster was well tolerated in both groups. These data support the use of Vaxelis® as a booster in mixed HV regimens.